Statistical study of teaching methods and their influence on students' performance - Oxana GRADINARI; Violeta BOGDANOVA (Acta et Commentationes, Sciences of Education, 2025)
This article is devoted to a statistical study of teaching methods and their influence on students' performance in mathematics at an educational institution in Bălți. The study analyzed the test results of 54 students, divided into two groups: 22 students were taught using traditional methods based on lectures and homework, while 17 students utilized the project method, which develops critical thinking and teamwork skills. To assess the statistical significance of the differences in performance, the one-way analysis of variance (ANOVA) and (Q) Rosenbaum criterion was applied. The results showed that the project-based learning method significantly improves students' mathematics performance compared to the traditional approach. The study demonstrated the importance of using diverse teaching methods to achieve higher academic outcomes.